Short-term outcomes of unfractionated heparin vs. low molecular weight heparin in trans-radial coronary angiography: a comparative study - Taha, Salma; Ibrahim Sakr, Mahmoud Ibrahim Mohamed; Abd El Salaam, Mohamed Salah El Deen; Ahmed, Mohamed Mahmoud; Abdelmegid, Mohamed Aboel-Kassem F. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTrans-radial access (TRA) for coronary angiography is preferred for its lower complication rates than trans-femoral access. However, radial artery occlusion (RAO) remains a significant concern.ObjectiveThe objective of this study was to assess the efficacy of low molecular weight heparin (LMWH) compared to unfractionated heparin (UFH) in preventing radial artery occlusion (RAO) and associated problems during trans-radial access (TRA) for coronary angiography.MethodsIn this moderate sized clinical prospective study conducted from March 2019 to January 2020 at Al Azhar Assiut University Hospital and Sohag Cardiac and GIT Center, 400 patients undergoing elective coronary angiography via TRA were divided into two groups. Group A (n = 200) received UFH, and Group B (n = 200) received LMWH (enoxaparin). Parameters assessed included radial artery diameter, flow volume, intima-media thickness (IMT), and complications post-procedure.ResultsExcept for gender distribution, no significant differences at baseline were identified between the groups. Although both groups showed slight changes in arterial diameter and flow volume with a small rise in IMT after 10 days, there were notable differences in radial artery occlusion rates. The UFH group had an occlusion rate of 3.5%, while the LMWH group had a rate of 0.5% (P = 0.032). The groups exhibited no significant difference in other consequences, such as hematoma and arteriovenous fistula.ConclusionsLMWH (enoxaparin) administration via the radial sheath during TRA is a safe and effective strategy for reducing the incidence of RAO compared with UFH without increasing other procedural complications. This suggests that LMWH may be preferred for patients undergoing TRA for coronary angiography to minimize the risk of RAO.